"Efectos Del Confinamiento Por Covid-19 En La Salud Mental De Los Estudiantes Universitarios: Una Revisión Narrativa De La Literatura" (2023)
The objective of this research is to describe the symptoms presented in university students during the mandatory confinement due to covid-19, to determine the strategies established by higher education institutions to provide both emotional and academic support to university students.